2007
DOI: 10.1007/s10663-007-9038-z
|View full text |Cite
|
Sign up to set email alerts
|

Wage differences between Austrian men and women: semper idem?

Abstract: Wage differentials, Wage inequality, Decomposition, J31, J71,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
2
20
0
7
Order By: Relevance
“…All these characteristics contribute significantly to the explanation of the gender wage gap. Our descriptive analyzes confirm earlier results, women earn on average less then men, they are on average better formally educated than men, but have on average less workplace experience, probably due to child bearing (Böheim et al 2007(Böheim et al , 2012Grünberger and Zulehner 2009;Pointner and Stiglbauer 2010). Taking observed differences between women and men into account, we find that about 40 % of the wage gap is due to observable differences in characteristics, i.e., fair discrimination.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…All these characteristics contribute significantly to the explanation of the gender wage gap. Our descriptive analyzes confirm earlier results, women earn on average less then men, they are on average better formally educated than men, but have on average less workplace experience, probably due to child bearing (Böheim et al 2007(Böheim et al , 2012Grünberger and Zulehner 2009;Pointner and Stiglbauer 2010). Taking observed differences between women and men into account, we find that about 40 % of the wage gap is due to observable differences in characteristics, i.e., fair discrimination.…”
Section: Discussionsupporting
confidence: 88%
“…The difference in mean wages in 2007 was about €3.3 per hour, and women earned on average some 19.1 % less than men, not accounting for differences in characteristics. This "raw" gap is smaller than in 1997, when it was about 23.3 % (Böheim et al 2007). Figure 1 plots the distribution of the log hourly wages of full-time employed men and women in the private and public sector.…”
Section: Data and Summary Statisticsmentioning
confidence: 93%
See 1 more Smart Citation
“…First, studies on the (general) gender wage differential in the Austrian labor market suggest an overall income gap of about 25 to 30 percent. For instance, a recent study by Böheim, Hofer and Zulehner (2007) reports an overall gender wage gap of about 25 percent and a share of discrimination of around 60 to 70 percent (see also Ponthieux and Meurs, 2005;Arulampalam, Booth and Bryan, 2007;Olivetti and Petrongolo, 2008; for similar evidence from the Austrian labor market). Further, they find that the wage differential increases with income (see also Arulampalam, Booth and Bryan, 2007;Olivetti and Petrongolo, 2008).…”
Section: > Tablementioning
confidence: 95%
“…Contrary to this evidence, García et al Böheim et al (2007) and Ortega (2007) reported that the gender pay gap is greater among better qualified workers, while Simó n (2006) found that the gap in pay between the best educated male and female workers was greater in Spain than in any other European country, except Ireland, although the gap was smaller among 20 less well-qualified workers. Palacio and Simó n (2002) and Cho (2007) reported that male-female pay inequality was greater in both Spain and Korea not only when the women concerned lacked educational qualifications, but also among female graduates.…”
mentioning
confidence: 91%